2022
DOI: 10.3389/fendo.2022.839360
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells in Thermogenic Adipose Depots: The Essential but Complex Relationship

Abstract: Brown adipose tissue (BAT) is a unique organ in mammals capable of dissipating energy in form of heat. Additionally, white adipose tissue (WAT) can undergo browning and perform thermogenesis. In recent years, the research community has aimed to harness thermogenic depot functions for new therapeutic strategies against obesity and the metabolic syndrome; hence a comprehensive understanding of the thermogenic fat microenvironment is essential. Akin to WAT, immune cells also infiltrate and reside within the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 119 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…All these genes were protein-coding genes, of which COX1 was reported that could regulate energy production in mitochondria and its impairment could result in reactive oxygen intermediates promoting oxidative stress [ 53 ], and UBB was an extrinsic substrate of the proteasome-dependent ubiquitin-fusion degradation pathway [ 54 ], and OAZI was demonstrated that its activity was associated with mitochondria [ 55 ], and NPFF was described that NPFF receptors were important for pubertal onset in pigs [ 56 ]. In addition, the signaling pathways of HKGs were investigated and found to be associated with various biological processes that sustain the basic cellular functions of life, including ribosome [ 57 ], spliceosome [ 58 ], thermogenesis [ 59 ], oxidative phosphorylation [ 60 ], and nucleocytoplasmic transport [ 61 ]. These results were consistent with previous reports [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these genes were protein-coding genes, of which COX1 was reported that could regulate energy production in mitochondria and its impairment could result in reactive oxygen intermediates promoting oxidative stress [ 53 ], and UBB was an extrinsic substrate of the proteasome-dependent ubiquitin-fusion degradation pathway [ 54 ], and OAZI was demonstrated that its activity was associated with mitochondria [ 55 ], and NPFF was described that NPFF receptors were important for pubertal onset in pigs [ 56 ]. In addition, the signaling pathways of HKGs were investigated and found to be associated with various biological processes that sustain the basic cellular functions of life, including ribosome [ 57 ], spliceosome [ 58 ], thermogenesis [ 59 ], oxidative phosphorylation [ 60 ], and nucleocytoplasmic transport [ 61 ]. These results were consistent with previous reports [ 62 ].…”
Section: Discussionmentioning
confidence: 99%